The Complete Python Course - Percival, Rob; Salvatierra, Jose (Packt Publishing, 2019)
Go from beginner to expert in Python by building projects. The best investment for your Python journey! About This Video Develop a lifelong love for programming with Python! From foundations to expert, learn about every major Python topic. Master Object-Oriented Programming and structure your Python programs like a professional. In Detail The course covers every major Python topic (including Object-Oriented Programming, Web Scraping, and even GUI development), and now includes even more content. Control your browser using Selenium, to scrape websites or even fill in forms Learn to interact with REST APIs and build a currency exchange program Create desktop GUIs using Tkinter, so your users can work with your applications very easily Start working with unit testing in Python by learning about the unit test library We've also completely re-recorded the course's introductory Python material, so it's even clearer and more straightforward! This course will take you from beginner to expert in Python, easily and quickly. We've ensured every piece of content is concise and straightforward and will never leave you confused. This course dives right into Python and makes you productive right from the start. This is the best investment you can make in your Python journey. Downloading the example code for this course: You can download the example code files for this course on GitHub at the following link: https://github.com/PacktPublishing/The-Complete-Python-Course . If you require support please email: customercare@packt.com.